Pengaruh Latihan Open Kinetic Chain Terhadap Kesembuhan Pasien Dengan Osteoarthritis di RSUD Dr. Harjono Ponorogo - Kevin Abi Agustian; Dwi Rosella K.S; Kingkinnarti Kingkinnarti (STIKes Ibnu Sina Ajibarang, 2024)
Background: Osteoathritis is a degenerative disease that is usually experienced by individuals due to the aging process. Osteoarthritis can limit and affect a person's activities. There is evidence that muscle dysfunction is involved in the pathogenesis of knee OA. The lower leg muscles are the natural support of the knee joint and improper alignment of the knee can originate proximally, and that poor force production due to muscle weakness can be a factor that ultimately causes stress on the knee. Muscles play a major role in joint structure and function, as demonstrated by the disuse of the quadriceps femoris muscle that accompanies knee joint pain. Quadriceps muscle weakness has been noted by the American Academy of Orthopedic Surgeons as a risk factor for structural damage to the knee joint. Muscle weakness affects the anteroposterior stability of the knee joint. and makes patients feel unstable, causing decreased self-confidence and decreased performance and independence in daily activities, causing disability and dysfunction in osteoarthritis knee patients. The main symptom that arises from Osteoarthritis is pain. Pain is the main problem in sufferers of knee osteoarthritis, and is generally related to activity and will recover when resting. Objective: This study aims to determine the effectiveness of the Open Kinetic Chain Exercise intervention on the recovery of patients with osteoarthritis. Method: This research uses a case report study with the aim of knowing the treatment of individuals before and after being given the intervention. Results: Providing TENS intervention and open kinetic chain exercises 4x, results in reduced pain intensity, increased joint range of motion and increased functional ability. Conclusion: Providing intervention in the form of TENS and Open Kinetic Chain Exercise has proven to be effective in reducing pain, increasing LGS and increasing functional activity in conditions of Osteoarthritis Knee.